Thermal Stability and Rheological Properties of Polyethylene (PE)/Polyvinylchloride (PVC)/Wood Composites - Wang, Xing; Yang, Bin; Xia, Ru; Miao, Ji-Bin; Qian, Jia-Sheng; Chen, Peng; Deng, Shuang-Quan (Journal of Research Updates in Polymer Science, 2013)
This paper investigated the thermorheological properties, thermal properties and flame retardant properties of wood-plastic composites (WPCs). With the addition of wood flour (WF), the rheological behavior became complexity. The critical frequency of shear-thinning phenomenon of the melt viscosity was shifted toward lower value. The temperature dependence of elastic modulus, loss modulus became more serious with the addition of WF. The Cole-Cole plot indicated the existence of complex multi-phase structure in the WPC melt. The CONE calorimetry results showed that ammonium polyphosphate (APP) had good flame retardancy through promoting the formation of the intumescent carbon layer. The present study will supply good insight into the optimization of WPC formulation.